“Energy, Economy, Environment, Wellbeing” the Role of Formal Languages For Finding and Implementing Solutions - Giannantoni, Corrado (Journal of Environmental Accounting and Management, 2026)
The paper aims at showing that the problems concerning the aspects mentioned in the title can better be analyzed by focusing on the formal languages adopted to describe them. This is because any formal language is always the faithful “reflex” of the subjacent mental categories aprioristically adopted to describe the surrounding world. At the same time, the recognized expressive capacity of any formal language decisively influences the way of thinking, decision making and acting. Up to know all the aforementioned aspects have usually been dealt with in terms of Traditional Differential Calculus (TDC), which however presents some unsolvable and/or intractable problems and, in some cases, it offers solutions characterized by a “drift” (with respect to experimental results), which often represents a “symptom” of possible “side effects”. A different formal language, however, is now contextually possible. It is precisely that which emerges from the original thermodynamic approach proposed by Boltzmann and Lotka and, afterwards, much more deeply developed by H. T. Odum. A new scientific approach that has more recently led to a formal language termed as Incipient Differential Calculus (IDC). The different solutions obtainable by adopting the two distinct formal languages, although with reference to the same problems, will be illustrated through the following ostensive examples: the research for equilibrium conditions in a free-market economy, the development of renewable energy sources, climate change forecasts, and some problems related to human health (for instance, new oncological therapies). The paper concludes by asking a basic question: “Where are we going?” In this respect the paper delineates three possible answers: i) a generalized persistence in the traditional formal approach (TDC); ii) some occasional adoptions of the innovative IDC approach; iii) more probably it may be expected the adoption of both approaches at the same time, so as to choose the optimal solutions on the basis of the corresponding experimental results.